TRANSPORTATION TIME DURATIONANALYSIS OF FISHERMEN CATCHES WAS LANDED ON DUMAI FISH FISHING PORT, OF RIAU PROVINCE - Yuli Yanti Siregar; Arthur Brown; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research was conducted at the Fish Landing Base, having its address at Jalan Pangkalan Sesai-Dumai, on 02-10 August 2019. The purpose of this research is to Analyze the time in each facility that is passed and Knowing the landing activity of catches While the benefits of this research are as a source of basic information to improve the time process of fishermen's catches so that the time is shorter and the level of freshness is more maintained. From the results of this study, Analysis of fishermen's catches needs to be known so that catches are more awake and the freshness of fish will be better when it arrives at consumers. The transporting time of fishermen's catches at Dumai City Fish Landing Base with a span of 72 hours - 120 hours (3-5 days) on sondong boats and on gill nets 96 hours - 120 hours (4-5 days). In addition, the freshness of fish is also supported by the ratio of the use of ice used by fishermen is 1: 2-1: 3 on sondong boats, while gill nets 1: 1 - 1: 4 the ratio of ice used. According to the Director General of POM, Dep. Kes 1987 Good use of ice can maintain the freshness of fish for 3-5 days.Keywords:Time Analysis, Gill Net and Sondong, Dirjen POM,Dep.Kes1987